Biochemical Parameters in Women with Polycystic Ovary Syndrome in Ajman, UAE - Gomathi, K; Shaafie, IA; Mummigatti, K; Shahid, S; Sreedharan, J (Nepal Journal of Obstetrics and Gynaecology, 2012)
Aims: Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting 5 -10% of women and is a major cause of anovulatory infertility. Prevalence varies among population based on genetic and environmental factors. Etiology of PCOS remains unknown but hyperandrogenism and insulin resistance have both been associated with PCOS. The aim of this study was to measure levels of Homocysteine and other biochemical parameters in women diagnosed with PCOS attending Gulf Medical College Hospital & Research Centre (GMCHRC), Ajman, UAE. Methods: Young women, aged between 18 and 35 years of age, diagnosed with PCOS (N =37), not on any treatment, attending GMCHRC were included in the study. Biochemical parameters were measured using standard procedures. Laboratory normal reference ranges were used for comparison. Results: 54 % of the women with PCOS were overweight or obese according to the Body mass index (BMI) and 51% had a waist circumference >88cm. Fasting and postprandial Glucose and Insulin levels and HOMA-IR were within the normal reference range indicating that no Insulin resistance was seen in these women. 40% of the women had a serum total Cholesterol level above 200 mg/dL, while Low Density Lipoprotein (LDL) Cholesterol was above and High Density Lipoprotein (HDL) cholesterol was lower than the desirable value. Serum Triacylglycerol was within the normal reference range. Serum Testosterone, Estradiol, Prolactin Thyroid Stimulating Hormone (TSH) and Plasma Homocysteine level were found to be within the normal reference ranges. Homocysteine levels correlated with Testosterone, total Cholesterol and LDL cholesterol levels. Conclusions: BMI was high in 54% of the women. No Insulin resistance was seen in these patients. Hormone levels and Homocysteine were within normal reference ranges. Dyslipidermia was observed. These findings differ from reports in literature where Insulin resistance, Hyperandrogenism and high Homocysteine levels have been associated with PCOS. NJOG 2011 Nov-Dec; 6 (2): 7-10 DOI: http://dx.doi.org/10.3126/njog.v6i2.6748